Contingent Liabilities for Infrastructure Projects : Implementing a Risk Management Framework for Governments - Lewis, Christopher M.; Mody, Ashoka (World Bank, Washington, DC, 2012)
To manage their exposure arising from guarantees to infrastructure projects, governments need to adopt modern risk management techniques. The authors introduce an integrated risk management system that draws on recent advances in the private sector. Adapted for use in the public sector, the system enables governments to budget for expected losses and to set aside reserves against unexpected losses, thus avoiding the budgetary stress associated with redirecting scarce public resources to cover a sudden increase in costs.